Disseminated Endometriosis and Low-Grade Endometrioid Stromal Sarcoma in a Patient with a History of Uterine Morcellation for Adenomyosis - Daniel P. Stefanko; Ramez Eskander; Omonigho Aisagbonhi (Case Reports in Obstetrics and Gynecology)
Morcellation of benign uterine tumors allows for removal of the tumors via minimally invasive laparoscopic procedures. However, in rare cases, morcellation has been associated with upstaging of unexpected malignancies. Morcellation has also been associated with dissemination of benign pathologic processes such as endometriosis and leiomyomas. Endometrial stromal sarcoma typically arises in the uterine cavity, although cases of extrauterine endometrioid stromal sarcoma arising out of foci of endometriosis have been reported. Dissemination of endometrial stromal sarcomas can be an unintended consequence of morcellation procedures, as can dissemination of endometriosis, from which endometrioid stromal sarcomas can arise. Herein, we report a case of a 55-year-old woman who was found to have disseminated endometriosis and low-grade endometrioid stromal sarcoma, with bowel and liver parenchymal metastasis, 7 years after undergoing supracervical hysterectomy with unconfined uterine morcellation for adenomyosis. Our case highlights the potential for malignant transformation of disseminated adenomyosis/endometriosis and the importance of patient counseling and shared decision-making prior to morcellation procedures.